ChemInform Abstract: Silver‐Mediated Synthesis of Indolizines via Oxidative C—H Functionalization and 5‐endo‐dig Cyclization. Issue 18 (May 2015) - Pandya, Amit N.; Fletcher, James T.; Villa, Eric M.; Agrawal, Devendra K.
Abstract The silver carbonate is recycled and reused to mediate the reaction with analogous reactivity.